Health-Related Physical Fitness as a Risk Factor for Falls in Elderly People Living in the Community: A Prospective Study in China - Duan, Hongxia; Wang, Hao; Bai, Yiwen; Lu, Yan; Xu, Xueping; Wu, Jing; Wu, Xubo (Frontiers in Public Health, 2022)
Objectives Health-related physical-fitness (HRPF) involves multi-components of physical functional tests and is reported to be associated with the risk of fall. The study sought to determine whether specific physical fitness components were stronger predictors of falls among elderly people. Methods This prospective cohort study involved 299 community residents age ≥60 years from Shanghai, China. The baseline data included comprehensive assessment of sociodemographic, clinical, and HRPF test. Subjects were followed for 1 year and were contacted by telephone to report falls. LASSO regression and Multivariate regression analysis were used to identify risk predictors of fall. In addition, we used receiver operating characteristic (ROC) curve analyses to determine whether the predictors have diagnostic. Results During the 1-year prospective fall assessment, 11.7% of these subjects experienced one or frequent falls. LASSO models revealed that age (=0.01) and 8-ft up-and-go test score (=0.06) were positively associated with falls, while activity-specific balance confidence (ABC; = −0.007) and 2-min step test score (= −0.005) were inversely related. The Area Under roc Curve (AUC) for a linear combination of age, ABC scale score, 2-min step test and 8-ft up-and-go test was 0.778 (95% confidence interval: 0. 700–0.857), which was superior to any of the variables taken alone. Conclusion Age, activity-specific balance confidence and fitness abnormalities were determined to contribute to the incident of falls. The value of 2-min step test score, and 8-ft up-and-go test score were the key HRPF components in predicting falls among elderly people.